2021
DOI: 10.1055/a-1673-1616
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Role of Systemic Inflammatory Indices in Infants with Moderate-to-Severe Hypoxic Ischemic Encephalopathy

Abstract: Aim: We aimed to determine the diagnostic role of systemic inflammatory (SI) incides in infants with moderate to severe HIE. We have also investigated the effect of hypothermia treatment (HT) over those indices. Method A retrospective cohort study of infants suffering from moderate-severe HIE was conducted in a tertiary level neonatal intensive care unit between September 2019 to March 2021. SI indices including systemic immune-inflammation index (SII), pan-immune-inflammation value (PIV), systemic inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
(46 reference statements)
0
14
0
2
Order By: Relevance
“…While the SII has been used for a long time in the evaluation of disease severity, course and treatment response in adult patient group in oncology practice, it has recently been shown to be associated with the identification of risk groups for COVID-19 and mortality 17 . It is known that it has recently been used to predict disease severity in diseases such as perinatal hypoxic ischemic encephalopathy and retinopathy in newborn babies 19,23 . In our study, SII was found to be significantly higher in babies born to COVID-19 PCR positive mothers compared to the control group, but it could not be shown to be an independent marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the SII has been used for a long time in the evaluation of disease severity, course and treatment response in adult patient group in oncology practice, it has recently been shown to be associated with the identification of risk groups for COVID-19 and mortality 17 . It is known that it has recently been used to predict disease severity in diseases such as perinatal hypoxic ischemic encephalopathy and retinopathy in newborn babies 19,23 . In our study, SII was found to be significantly higher in babies born to COVID-19 PCR positive mothers compared to the control group, but it could not be shown to be an independent marker.…”
Section: Discussionmentioning
confidence: 99%
“…Hemogram parameters evaluated in the patient and control groups were taken in the postnatal first 6 hours. It was calculated with the ratio of NLR-absolute neutrophil count (N; 10 9 /L) to the absolute lymphocyte count (L; 10 9 /L) (with the formula NLR=N/L), the ratio of PLR-absolute platelet count (P; 10 9 /L) to the absolute lymphocyte count (L; 10 9 /L) (with the formula PLR=P/L) and the multiplication of SII-NLR value by absolute platelet count (with SII=NLR×P/1000 formula) 19 .…”
Section: Systemic Immune-inflammation Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anne ya da fetustaki gaz değişimindeki bozulma metabolik asidoza neden olur. Bu metabolik asidoz ise düşük Apgar skoru, hipoksik iskemik ensefalopati, intrakranial kanama, nekrotizan enterokolit, sepsis, solunum sıkıntısı, nöbet, serebral palsi, nörogelişimsel gelişimde bozulma ve ölümle ilişkilidir (1)(2)(3)(4). Kritik yenidoğan bebeklerde yaygın olarak kullanılan kan gazındaki parametreler, hipotermi tedavisi kararını vermede ve hastanın prognozunu belirlemede klinisyene değerli bilgiler vermektedir (5).…”
Section: Introductionunclassified
“…Term olarak doğan yenidoğan bebeklerde umbilikal arterdeki düşük pH ve baz fazlası (BE) ve daha yüksek parsiyel arteriyel karbondioksit basıncı (pCO 2 ) değerlerinin hipoksik iskemik ensefalopati, kardiyopulmoner resusitasyon ve nöbet sıklığında artış ile ilişkili olduğu gösterilmiştir (2,6). Umbilikal ven ya da arter pH değerinin <7,00 olmasının mortalite ile ilişkili olduğu rapor edilmiştir (7).…”
Section: Introductionunclassified